Juridical Analysis of Urgent Termination of Employment at PT BFI Finance Indonesia Tbk Based on Decision Number 5/Pdt.Sus-PHI/2025/PN Plk - Ika Julina; Fransisco Fransisco; Vicka Prama Wulandari; Joanita Jalianery (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
Termination of Employment on urgent grounds has generated debate in judicial practice because the conceptual boundaries of what constitutes “urgent” are not yet fully clear. Previous studies have analyzed the regulation of urgent termination normatively; however, they have not examined how judges apply the criteria of urgency in judicial practice and its relationship with trust as the foundation of the employment relationship. This study analyzes Decision Number 5/Pdt.Sus-PHI/2025/PN Plk to identify the judges’ considerations in assessing urgent termination, using a normative juridical method with a case approach. The results show that the Panel of Judges applied a cumulative four-pillar approach: violation of the legality principle under the Fiduciary Security Law, ultra vires actions, a concrete loss of Rp120,000,000.00, and a breach of fiduciary duty due to a conflict of interest. Urgent termination does not require a warning letter because such conduct fundamentally damages trust, in accordance with the provisions of Law Number 6 of 2023 and Government Regulation Number 35 of 2021. The decision clarifies the limits of vicarious liability, which does not apply to actions that harm the company, with the consequence of limited compensation without severance pay and long-service awards.